Cross-country analysis of sustainable innovation and female entrepreneurship and their influence on the presence of women in managerial positions - Inna Alexeeva-Alexeev; Pilar Guaita-Fernandez; Cristina Mazas-Perez-Oleaga (Sustainable Technology and Entrepreneurship)
Despite the global increase of women in business, there is still a very small proportion of female business leaders, although the distribution varies greatly by region and sector. Considering innovation, in its many forms, as well as female entrepreneurship, both considered as a path towards sustainability, the question arises as to whether this drive for sustainability leads to a greater presence of female CEOs. Current studies predominantly examine the impact of women's presence on a company's economic and financial performance, as well as any potential effects on its innovation strategy. However, the examination of factors that help understand the economic and business context influencing the presence of women in leadership roles is often overlooked. This empirical study fills this gap by exploring the micro and macro context influencing the presence of female CEOs in innovative firms worldwide stressing the influence of female owners. The sample comprises 107,026 companies from manufacturing and service industries in 118 countries, from 2007 to 2023, data obtained from the World Bank Enterprise Surveys. The econometric model applied is logistic regression with clustered standard errors. The study contains six estimations generating strong evidence supporting most of the formulated hypotheses. Findings suggest women CEOs are likely to lead women-owned firms which promote (sustainable) innovation through developing new products for new markets, allocating less investment in R&D, product innovation and business processes, although with some nuances. Other important factors to consider are productivity, sales strategy, firm size, sector, and socio-economic context with a gender focus.